Formation of creativity characteristics in students of higher education organization based on CTEAM educational technology design method - Tolipova Ozoda Ikromovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article provides information about the reforms being carried out with the aim of radically changing the new Uzbek education system, integrating it with international standards, training qualified personnel who will meet the requirements of the labor market, and bringing up a new generation that will implement the idea of ​​the Third Renaissance.